Steady-state economics - Daly, Herman E. (Washington, D.C. Island Press, 1991)
First published in 1977, this volume caused a sensation because of Daly's radical view that'enough is best.'Today, his ideas are recognized as the key to sustainable development, and Steady-State Economics is universally acknowledged as the leading book on the economics of sustainability.
Keywords: Desarrollo económico -- Aspectos ambientales; Historia económica; Estancamiento (Economía); Desarrollo económico -- Aspectos éticos